PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF MATEMATIKA KELAS V SEKOLAH DASAR - Yus Annisa Achsanti; Dina Prasetyowati; Fenny Roshayanti (STKIP Subang, 2023)
The lack of active participation and involvement of students in the learning process causes the learning outcomes of fifth-grade elementary school students to be low. Therefore teachers need to apply learning models that can involve students in the learning process. One learning model that can increase active participation and student involvement is the Problem-Based Learning model. This study uses a quantitative approach with descriptive analysis, normality test, and t-test on cognitive outcomes students data through pretest and posttest before and after the application Problem-Based Learning model. Based on the findings of the researcher applying, the Problem-Based Learning learning model can improve cognitive mathematics learning outcomes in the material for presenting data to fifth-grade elementary school students.